Wireless charging in powered prosthetics - Hilmar Þór Pétursson 1991- (2020)
This project is done as a thesis for BSc in Applied electrical engineering at Reykjavík University Iceland at the behalf of Össur Iceland with funding and assistance provided. This thesis is worked over a 12 week period during the summer semester of 2020. The objective of this thesis is to provide a proof of concept for the possibility of wireless charging of powered prosthetics built by Össur. The charging must be proven to be possible with an acceptable amount of power, which would be at the minimum 20W but preferably 30 - 40W with a voltage output of 19-24V. An equally important part is the safety of the device, it must be tested to show the possible risks and suggestions should be made to ensure safety without compromising the power output. A prototype must be built into an Össur prosthetic and tested rigorously to ensure all design parameters are fulfilled. Össur hf